Pengaruh Celebrity Endorser terhadap Keputusan Pembelian Produk di Indonesia (Penelitian Online) - Salim, Muhartini; Bachri, Syamsul; Darmansyah (Jurnal Aplikasi Manajemen, 2014)
The purpose of this study was to analyze the influence of buying decision product in Indonesian. Variables identified in the survey is the Celebrity Endorser and Buying Decision. The respondents consumers product in indonesian. This research was conducted online are spread throughout the Indonesian region. Data were collected by questionnaires distributed directly to the respondents, data used is primary data that is by distributing questionnaires to 300 respondents. The sampling technique used directly nonprobability sampling is purposive sampling data. The results show that the Celebrity Endorser positive influence on the Buying Decision. because all indicators simultanly celebrity endoser can influence purchasing decisions.